Peculiarities of Enterprises Functioning Under Conditions of Cyclicality of the Economy - Rudenko, Alexander Alekseevich; Iskoskov, Maxim Olegovich; Antipov, Dmitry Vyacheslavovich; Polyakova, Tatyana Valerievna; Zaharov, Sergey Olegovich (International Journal of Economics and Financial Issues, 2016)
It is necessary to note that under contemporary conditions of economic management that is characterized by a high level of indefiniteness of the market environment, there is a potential risk of a decline in the activeness in economy on the macro level to the level that is below admissible. On the contrary, the interest to problems related to providing stable economic development of enterprises under conditions of unbalanced state of economy sharply grows. Under these conditions special importance is acquired by the search for regularities of economy functioning for the future development of efficient organizational and economic mechanism that can provide competitive functioning of integrated structures of the power engineering at any phase of the economic cycle. Herewith, the crisis of 2008 had a considerable unfavorable impact on the whole Russian industry. Keywords: functioning of enterprises; business cycle; power engineering; competitiveness; post-crisis period JEL Classifications: E32, E66, L26